El uso de recursos audiovisuales en el aprendizaje significativo de los estudiantes de la carrera de Comunicación Social de la Universidad Técnica de Babahoyo Ext- Quevedo semestre a 2020 - Oquendo Moncerrate, Angie Jarixa (2021)
The audiovisual media seek to facilitate dialogue, expression and participation of the main actors of the university classroom, both teachers and students, in the adoption of new practices that favor the development of classes and allow a better meaningful learning. The present study aimed to determine the use of audiovisual resources in the meaningful learning of students of the Social Communication Career of the Technical University of Babahoyo Ext-Quevedo in 2020. It addresses a diagnosis of the audiovisual resources that influence the meaningful learning of students. It allows to know how important audiovisual resources are within the educational field, treating them both from the point of view of teaching and learning. The results indicate that the use of audiovisual media has a positive impact on the significant learning of students of the Social Communication Career. This study contributes to raise the action of the teacher regarding the optimal use of educational audiovisual media.